Planification spatiale et agriculture urbaine. L’exemple de l’agglomération tourangelle - Céline Tanguay; Jean Louis Yengué; José Serrano (VertigO, 2018)
For the next decades, two strong societal challenges will have to be taken up: decently feeding the 10 billion people and ensuring a quality of life in overcrowded cities. Feeding the planet refers to the preservation of farmland, the latter being heavily threatened by urban extensions. Moreover, the well-being in cities can be partly assured by the elements of Nature among which the vegetable gardens and other elements of urban agriculture are included. We know that the maintaining of urban agriculture is one of the solutions to reconcile demographic growth, food self-sufficiency and well-being. Despite the growing number of initiatives, the implementation of an urban agriculture project is complex and never granted. Taking Tours (France) as an example, this article decrypts the fabrication of such a project, both politically and technically. It shows that feeding urban people is only a pretext to answer economic (structuring a sector), social (social cohesion) and environmental (biodiversity, protection of soil and groundwater, etc.) issues. This is how all urban development actors will be mobilized, guaranteeing the success of an urban agriculture project. This multifunctional vision of the territory makes it possible to overcome the still strong compartmentalization between environmental and food while the underlying aims are convergent. We also propose the idea of joining the purpose of preserving biodiversity to the sufficiency by creating a "green, blue and food belt" (TVBA).